Synthesis of La0.7Sr0.3MnO3 at 800 degrees C using citrate gel method - Ravi, V.; Kulkarni, S. D.; Samuel, V.; Kale, Sangeeta N.; Mona, J.; Rajgopal, R.; Daundkar, A.; Lahoti, P. S.; Joshi, Rakesh S. (Ceramics International, 2007)
Manganite systems have been of considerable interest in the recent past due to their potential to operate in wide property range and also to serve as effective magnetic sensing and storing devices when synthesized using stringent conditions. We report a novel citrate gel method, in which La0.7Sr0.3MnO3 system has been synthesized at temperature 800 degrees C (LSMO800) with the synthesis duration is 6 h. The results have been compared with the sample synthesized at 1050 degrees C (LSMO1050). The synthesized bulk polycrystalline sample shows single-phase nature with the increase in particle size from similar to 50 nm to 300 nm with the increase in the sintering temperature. The magnetization data for LSMO800 shows well-defined hysteresis with saturation magnetization at around 1800 Oe and Curie temperature at 360 K, which is slightly lower than that of LSMO1050, which is 375 K. The results can be well attributed to the grain boundary effects. (C) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Citrate gel method; CMR; Oxides

La0.67Ce0.03Sr0.3MnO3-coupled microwave assisted ultra-fast synthesis of nanocrystalline cobalt oxide and Bismuth oxide - Rajagopal, Rajashree; Mona, J.; Joshi, Rakesh S.; Kale, Sangeeta N.; Pradhan, Sivararn; Gaikwad, A. B.; Ravi, V. (Materials Letters, 2008)
Bismuth hydroxide and Cobalt hydroxide gels were freshly prepared by adding aqueous sodium hydroxide to their corresponding nitrates under basic conditions. Then they were oven dried at 373 K and found to be amorphous in X-ray diffraction (XRD) study. They crystallized into their respective oxides by microwave irradiation (2.45 GHz) in merely 2 min using La0.67Ce0.03Sr0.3MnO3 (LCSMO) as couplant in a microwave domestic oven (similar to 100 W). This is the lowest temperature treatment and synthesis time so far reported in the literature for the formation of these systems. Formation of nanocrystallites of Bi2O3 (10 nm) and Co3O4 (15 nm) has been confirmed by XRD. Normally these hydroxides produce oxides only on heating at temperature >673 K or digesting them at 373 K for 4 - 6 hours as reported by us earlier. Microwave assisted heating proves to be a novel technology whose applications can be carefully harnessed due to its unique effects compared to the conventional heating, such as rapid volumetric heating, shortened reaction time and energy saving. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; Manganites; Microwave; Oxides

Microwave assisted low temperature rapid synthesis of manganite system using La0.67Ce0.03Sr0.3MnO3 mini-cavity furnace - Kale, Sangeeta N.; Rajagopal, Rajashree; Mona, J.; Londhe, D. P.; Joshi, Rakesh S.; Jagadale, Tushar C.; Satyanarayana, C.; Ravi, V. (Materials Letters, 2008)
Amorphous La0.7Sr0.3MnO3 (LSMO) and La0.7Ca0.3MnO3 (LCMO) precursor powders synthesized by the citrate gel method at 673 K, have been found to crystallize by microwave irradiation in just 60 s using La0.67Ce0.03Sr0.3MnO3 (Ce-LSMO) as couplant. This is the lowest temperature treatment and synthesis time so far reported in literature for the fort-nation of manganite systems. Using ceramic route, the same amorphous samples crystallize on heat treatment only at temperatures greater than 1000 K. The microwave heating through this method is novel and has tremendous potential for accelerating the evolution of the product phase in very shorter durations, with just low temperature processing of the precursors, which cannot be realized in normal process. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; LSMO; Manganites; Microwave; Oxides

Alpha-geminal dihydroxymethyl piperidine and pyrrolidine iminosugars: synthesis, conformational analysis, glycosidase inhibitory activity, and molecular docking studies - Pawar, Nitin J.; Parihar, Vijay Singh; Chavan, Sanjay T.; Joshi, Rakesh S.; Joshi, Pranaya V.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2012)
The Jocic-Reeve and Corey-Link type reaction of dichloromethyllithium with suitably protected 5-keto-hexofuranoses followed by treatment with sodium azide and sodium borohydride reduction gave 5-azido-5-hydroxylmethyl substituted hexofuranoses 7a-c with required geminal dihydroxymethyl group. Removal of protecting groups and converting the C-1 anomeric carbon into free hemiacetal followed by intramolecular reductive aminocyclization with in situ generated C5-amino functionality afforded corresponding 5C-dihydroxymethyl piperidine iminosugars 2a-c. Alternatively, removal of protecting groups in 7b and 7c and chopping of C1-anomeric carbon gave C2-aldehyde that on intramolecular reductive aminocyclization with CS-amino gave 4C-dihydroxyrnethyl pyrrolidine iminosugars 1b and 1c, respectively. On the basis of the H-1 NMR studies, the conformations of 2a/2b were assigned as C-4(1) and that of 2c as C-1(4). The glycosidase inhibitory activities of all five iminosugars were studied with various glycosidase enzymes and compared with natural o-g/uco-l-deoxynojirimycin (DNJ). All the five compounds were found to be potent inhibitors of rice alpha-glucosidase with K-i and IC50 values in the nanomolar concentration range. Iminosugars 2b and 1b were found to be more potent inhibitors than their parent iminosugar. These results were substantiated by in silico molecular docking studies.

Complementation of intramolecular interactions for structural-functional stability of plant serine proteinase inhibitors - Joshi, Rakesh S.; Mishra, Manasi; Suresh, C. G.; Gupta, Vidya S.; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2013)
Background: Plant protease inhibitors (PIs) constitute a diverse group of proteins capable of inhibiting proteases. Among Pls, serine Pls (SPIs) display stability and conformational restrictions of the reactive site loop by virtue of their compact size, and by the presence of disulfide bonds, hydrogen bonds, and other weak interactions. Scope of review: The significance of various intramolecular interactions contributing to protein folding mechanism and their role in overall stability and activity of SPIs is discussed here. Furthermore, we have reviewed the effect of variation or manipulation of these interactions on the activity/stability of SPIs. Major conclusions: The selective gain or loss of disulfide bond(s) in SPIs can be associated with their functional differentiation, which is likely to be compensated by non-covalent interactions (hydrogen bonding or electrostatic interactions). Thus, these intramolecular interactions are collectively responsible for the functional activity of SPIs, through the maintenance of scaffold framework, conformational rigidity and shape complementarities of reactive site loop. General significance: Structural insight of these interactions will provide an in-depth understanding of kinetic and thermodynamic parameters involved in the folding and stability mechanisms of SPIs. These features can be explored for engineering canonical SPIs for optimizing their overall stability and functionality for various applications. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Disulfide bond; hydrogen bonding; Intramolecular weak interaction; Protease; Reactive site loop; Serine proteinase inhibitor

Differential protease activity augments polyphagy in helicoverpa armigera - Chikate, Yojana R.; Tamhane, V. A.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Insect Molecular Biology, 2013)
Helicoverpa armigera (Lepidoptera: Noctuidae) and other polyphagous agricultural pests are extending their plant host range and emerging as serious agents in restraining crop productivity. Dynamic regulation, coupled with a diversity of digestive and detoxifying enzymes, play a crucial role in the adaptation of polyphagous insects. To investigate the functional intricacy of serine proteases in the development and polyphagy of H.armigera, we profiled the expression of eight trypsin-like and four chymotrypsin-like phylogenetically diverse mRNAs from different life stages of H.armigera reared on nutritionally distinct host plants. These analyses revealed diet- and stage-specific protease expression patterns. The trypsins expressed showed structural variations, which might result in differential substrate specificity and interaction with inhibitors. Protease profiles in the presence of inhibitors and their mass spectrometric analyses revealed insight into their differential activity. These findings emphasize the differential expression of serine proteases and their consequences for digestive physiology in promoting polyphagy in H.armigera.
Keywords: adaptation; chymotrypsin; Helicoverpa armigera; polyphagy; Trypsin

Proteomic analysis of protease resistant proteins in the diabetic rat kidney - Bansode, Sneha B.; Chougale, Ashok D.; Joshi, Rakesh S.; Giri, Ashok P.; Bodhankar, Subhash L.; Harsulkar, Abhay M.; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2013)
Glycation induced protein aggregation has been implicated in the development of diabetic complications and neurodegenerative diseases. These aggregates are known to be resistant to proteolytic digestion. Here we report the identification of protease resistant proteins from the streptozotocin induced diabetic rat kidney, which included enzymes in glucose metabolism and stress response proteins. These protease resistant proteins were characterized to be advanced glycation end products modified and ubiquitinated by immunological and mass spectrometry analysis. Further, diabetic rat kidney exhibited significantly impaired proteasomal activity. The functional analysis of identified physiologically important enzymes showed that their activity was reduced in diabetic condition. Loss of functional activity of these proteins was compensated by enhanced gene expression. Aggregation prone regions were predicted by in silico analysis and compared with advanced glycation end products modification sites. These findings suggested that the accumulation of protein aggregates is an inevitable consequence of impaired proteasomal activity and protease resistance due to advanced glycation end products modification. Molecular & Cellular Proteomics 12: 10.1074/mcp.M112.020651, 228-236, 2013.

Structural-functional insights of single and multi-domain capsicum annuum protease inhibitors - Mishra, Manasi; Joshi, Rakesh S.; Gaikwad, Sushama M.; Gupta, Vidya S.; Giri, Ashok P. (Biochemical and Biophysical Research Communications, 2013)
Pin-II protease inhibitors (PIs) are the focus of research interest because of their large structural-functional diversity and relevance in plant defense. Two representative Capsicum annuum PI genes (CanPI-15 and -7) comprising one and four inhibitory repeat domains, respectively, were expressed and recombinant proteins were characterized. beta-Sheet and unordered structure was found predominant in CanPI-15 while -7 also displayed the signatures of polyproline fold, as revealed by circular dichroism studies. Inhibition kinetics against bovine typsin indicated three times higher potency of CanPI-7 (K-i similar to 57 mu M) than -15 (similar to 184 mu M). Activity and structural stability of these CanPIs were revealed under various conditions of pH, temperature and denaturing agent. Structure prediction, docking studies with proteases and mass spectroscopy revealed the organization of multiple reactive site loops of multi domain PIs in space as well as the steric hindrances imposed while binding to proteases due to their close proximity. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: CanPI; Circular dichroism; Disulfide bonding; Potato type-II protease inhibitors; Protein stability

Differential antibiosis against helicoverpa armigera exerted by distinct inhibitory repeat domains of capsicum annuum proteinase inhibitors - Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Phytochemistry, 2014)
Plant defensive serine proteinase inhibitors (Pis) are known to have negative impact on digestive physiology of herbivore insects and thus have a crucial role in plant protection. Here, we have assessed the efficacy and specificity of three previously characterized inhibitory repeat domain (IRD) variants from Capsicum annuum PIs viz., IRD-7, -9 and -12 against gut proteinases from Helicoverpa armigera. Comparative study of in silico binding energy revealed that IRD-9 possesses higher affinity towards H. armigera serine proteinases as compared to IRD-7 and -12. H. armigera fed on artificial diet containing 5 TIU/g of recombinant IRD proteins exhibited differential effects on larval growth, survival rate and other nutritional parameters. Major digestive gut trypsin and chymotrypsin genes were down regulated in the IRD fed larvae, while few of them were up-regulated, this indicate alterations in insect digestive physiology. The results corroborated with proteinase activity assays and zymography. These findings suggest that the sequence variations among Pis reflect in their efficacy against proteinases in vitro and in vivo, which also could be used for developing tailor-made multi-domain inhibitor gene(s). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Capsicum annuum; Helicoverpa armigera; Inhibitory repeat domain; Proteases; Proteinase inhibitors

Molecular investigations of protriptyline as a multi-target directed ligand in alzheimer's disease - Bansode, Sneha B.; Jana, Asis K.; Batkulwar, Kedar B.; Warkad, Shrikant D.; Joshi, Rakesh S.; Sengupta, Neelanjana; Kulkarni, Mahesh J. (Plos One, 2014)
Alzheimer's disease (AD) is a complex neurodegenerative disorder involving multiple cellular and molecular processes. The discovery of drug molecules capable of targeting multiple factors involved in AD pathogenesis would greatly facilitate in improving therapeutic strategies. The repositioning of existing non-toxic drugs could dramatically reduce the time and costs involved in developmental and clinical trial stages. In this study, preliminary screening of 140 FDA approved nervous system drugs by docking suggested the viability of the tricyclic group of antidepressants against three major AD targets, viz. Acetylcholinesterase (AChE), beta-secretase (BACE-1), and amyloid beta (A beta) aggregation, with one member, protriptyline, showing highest inhibitory activity. Detailed biophysical assays, together with isothermal calorimetry, fluorescence quenching experiments, kinetic studies and atomic force microscopy established the strong inhibitory activity of protriptyline against all three major targets. The molecular basis of inhibition was supported with comprehensive molecular dynamics simulations. Further, the drug inhibited glycation induced amyloid aggregation, another important causal factor in AD progression. This study has led to the discovery of protriptyline as a potent multi target directed ligand and established its viability as a promising candidate for AD treatment.

Remarkable efficiency of a pin-II proteinase inhibitor sans two conserved disulfide bonds is due to enhanced flexibility and hydrogen bond density in the reactive site loop - Joshi, Rakesh S.; Mishra, Manasi; Tamhane, Vaijayanti A.; Ghosh, Anirban; Sonavane, Uddhavesh; Suresh, C. G.; Joshi, Rajendra; Gupta, Vidya S.; Giri, Ashok P. (Journal of Biomolecular Structure & Dynamics, 2014)
Capsicum annuum (L.) expresses diverse potato type II family proteinase inhibitors comprising of inhibitory repeat domain (IRD) as basic functional unit. Most IRDs contain eight conserved cysteines forming four disulfide bonds, which are indispensible for their stability and activity. We investigated the functional significance of evolutionary variations in IRDs and their role in mediating interaction between the inhibitor and cognate proteinase. Among the 18 IRDs encoded by C. annuum, IRD-7, -9, and -12 were selected for further characterization on the basis of variation in their reactive site loop, number of conserved cysteine residues, and higher theoretical G(bind) for interaction with Helicoverpa armigera trypsin. Moreover, inhibition kinetics showed that IRD-9, despite loss of some of the disulfide bonds, was a more potent proteinase inhibitor among the three selected IRDs. Molecular dynamic simulations revealed that serine residues in the place of cysteines at seventh and eighth positions of IRD-9 resulted in an increase in the density of intramolecular hydrogen bonds and reactive site loop flexibility. Results of the serine residues chemical modification also supported this observation and provided a possible explanation for the remarkable inhibitory potential of IRD-9. Furthermore, this natural variant among IRDs showed special attributes like stability to proteolysis and synergistic inhibitory effect on other IRDs. It is likely that IRDs have coevolved selective specialization of their structure and function as a response towards specific insect proteases they encountered. Understanding the molecular mechanism of pest protease-plant proteinaceous inhibitor interaction will help in developing effective pest control strategies.An animated interactive 3D complement (I3DC) is available in Proteopedia at http://proteopedia.org/w/Journal:JBSD:39
Keywords: Capsicum annuum; Helicoverpa armigera; Proteases; Proteinase inhibitor

Resistance through inhibition: ectopic expression of serine protease inhibitor offers stress tolerance via delayed senescence in yeast cell - Joshi, Rakesh S.; Tanpure, Rahul S.; Singh, Rajan Kumar; Gupta, Vidya S.; Giri, Ashok P. (Biochemical and Biophysical Research Communications, 2014)
Protease inhibitors have been known to confer multiple stress tolerance in transgenic plants. We have assessed growth of yeast (Pichia pastoris GS115) strains expressing inhibitory repeat domains (PpIRD(+)) of previously characterized Capsicum annuum protease inhibitors under high salt, heavy metal and oxidative stress. PpIRD(+) strains exhibited multiple stress tolerance and showed differential molecular responses at transcriptional and translational level on exposure to stress inducing agents like heavy metal, high salt and H2O2. PpIRD(+) strains display significant reduction in metacaspase (Yca1) activity, the key enzyme in apoptosis, indicates the possibility of cross reactivity of IRDs (serine protease inhibitor) with cysteine proteases. PpIRD(+) and Saccharomyces cerevisiae knockout with Yca1 (Delta Yca1) strain showed similar growth characteristics under stress, which indicated the delayed senescence due to cellular metacaspase inhibition. Molecular docking study showed a close proximity of IRDs reactive site and the active site of metacaspase in the complex that signified their strong interactions. Maintenance of GAPDH activity, primary target of metacaspase, in PpIRD(+) strain evidenced the inhibition of metacaspase activity and survival of these cells under stress. This report demonstrates a potential molecular mechanism of protease inhibitor-based multiple stress tolerance in yeast strains. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Metacaspase; Multiple stress tolerance; protease inhibitor; Yeast

Way toward ``dietary pesticides'': molecular investigation of insecticidal action of caffeic acid against helicoverpa armigera - Joshi, Rakesh S.; Wagh, T. P.; Sharma, N.; Mulani, Fayaj A.; Sonavane, U.; Thulasiram, H. V.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Agricultural and Food Chemistry, 2014)
Bioprospecting of natural molecules is essential to overcome serious environmental issues and pesticide resistance in insects. Here we are reporting insights into insecticidal activity of a plant natural phenol. In silico and in vitro screening of multiple molecules supported by in vivo validations suggested that caffeic acid (CA) is a potent inhibitor of Helicoverpa armigera gut proteases. Protease activity and gene expression were altered in CA-fed larvae. The structure-activity relationship of CA highlighted that all the functional groups are crucial for inhibition of protease activity. Biophysical studies and molecular dynamic simulations revealed that sequential binding of multiple CA molecules induces conformational changes in the protease(s) and thus lead to a significant decline in their activity. CA treatment significantly inhibits the insect's detoxification enzymes, thus intensifying the insecticidal effect. Our findings suggest that CA can be implicated as a potent insecticidal molecule and explored for the development of effective dietary pesticides.
Keywords: Caffeic acid; Helicoverpa armigera; insecticidal activity; protease inhibitor

Cathepsins of lepidopteran insects: aspects and prospects - Saikhedkar, Nidhi; Summanwar, Aarohi; Joshi, Rakesh S.; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2015)
Molecular understanding of lepidopteran physiology has revealed that proteases consist of one of the central regulatory/reacting system for insect growth and survival. Among the various proteases, cathepsins are the most crucial cellular proteases, which play vital roles during insect development. In the present review, we have discussed various aspects of the lepidopteran insect cathepsins, emphasizing their roles in processes like development, growth, metamorphosis, apoptosis and immunity. Cathepsins are categorized into different types on the basis of their sequence diversification, leading to variation in structure and catalytic function. Cathepsins exhibit tissue and stage specific expression pattern which is fine-tuned by a delicate balance of expression, compartmentalization, zymogen activation, inhibition by protein inhibitors and degradation. The indispensability of cathepsins as cellular proteases in the above mentioned processes proposes them as novel targets for designing effective and specific insect controlling strategies. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Apoptosis; Cathepsin; Cysteine/aspartate protease; Development; Lepidoptera; Pest control; Stress response

Ecological turmoil in evolutionary dynamics of plant-insect interactions: defense to offence - Mishra, Manasi; Lomate, Purushottam R.; Joshi, Rakesh S.; Punekar, Sachin A.; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
Available history manifests contemporary diversity that exists in plant-insect interactions. A radical thinking is necessary for developing strategies that can co-opt natural insect-plant mutualism, ecology and environmental safety for crop protection since current agricultural practices can reduce species richness and evenness. The global environmental changes, such as increased temperature, CO (2) and ozone levels, biological invasions, land-use change and habitat fragmentation together play a significant role in re-shaping the plant-insect multi-trophic interactions. Diverse natural products need to be studied and explored for their biological functions as insect pest control agents. In order to assure the success of an integrated pest management strategy, human activities need to be harmonized to minimize the global climate changes. Plant-insect interaction is one of the most primitive and co-evolved associations, often influenced by surrounding changes. In this review, we account the persistence and evolution of plant-insect interactions, with particular focus on the effect of climate change and human interference on these interactions. Plants and insects have been maintaining their existence through a mutual service-resource relationship while defending themselves. We provide a comprehensive catalog of various defense strategies employed by the plants and/or insects. Furthermore, several important factors such as accelerated diversification, imbalance in the mutualism, and chemical arms race between plants and insects as indirect consequences of human practices are highlighted. Inappropriate implementation of several modern agricultural practices has resulted in (i) endangered mutualisms, (ii) pest status and resistance in insects and (iii) ecological instability. Moreover, altered environmental conditions eventually triggered the resetting of plant-insect interactions. Hence, multitrophic approaches that can harmonize human activities and minimize their interference in native plant-insect interactions are needed to maintain natural balance between the existence of plants and insects.
Keywords: Climatic change; Co-evolution; Ecosystem; Human interference; Plant-insect interaction

Structural features of diverse Pin-II proteinase inhibitor genes from capsicum annuum - Mahajan, Neha S.; Dewangan, Veena; Lomate, Purushottam R.; Joshi, Rakesh S.; Mishra, Manasi; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
The proteinase inhibitor (PI) genes from Capsicum annuum were characterized with respect to their UTR, introns and promoter elements. The occurrence of PIs with circularly permuted domain organization was evident. Several potato inhibitor II (Pin-II) type proteinase inhibitor (PI) genes have been analyzed from Capsicum annuum (L.) with respect to their differential expression during plant defense response. However, complete gene characterization of any of these C. annuum PIs (CanPIs) has not been carried out so far. Complete gene architectures of a previously identified CanPI-7 (Beads-on-string, Type A) and a member of newly isolated Bracelet type B, CanPI-69 are reported in this study. The 5' UTR (untranslated region), 3'UTR, and intronic sequences of both the CanPI genes were obtained. The genomic sequence of CanPI-7 exhibited, exon 1 (49 base pair, bp) and exon 2 (740 bp) interrupted by a 294-bp long type I intron. We noted the occurrence of three multi-domain PIs (CanPI-69, 70, 71) with circularly permuted domain organization. CanPI-69 was found to possess exon 1 (49 bp), exon 2 (551 bp) and a 584-bp long type I intron. The upstream sequence analysis of CanPI-7 and CanPI-69 predicted various transcription factor-binding sites including TATA and CAAT boxes, hormone-responsive elements (ABRELATERD1, DOFCOREZM, ERELEE4), and a defense-responsive element (WRKY71OS). Binding of transcription factors such as zinc finger motif MADS-box and MYB to the promoter regions was confirmed using electrophoretic mobility shift assay followed by mass spectrometric identification. The 3' UTR analysis for 25 CanPI genes revealed unique/distinct 3' UTR sequence for each gene. Structures of three domain CanPIs of type A and B were predicted and further analyzed for their attributes. This investigation of CanPI gene architecture will enable the better understanding of the genetic elements present in CanPIs.
Keywords: CanPI; Capsicum; Gene architecture; Promoter; Proteinase inhibitor

Comparative functional characterization of eugenol synthase from four different ocimum species: implications on eugenol accumulation - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Singh, Priyanka A.; Joshi, Rakesh S.; Mulani, Fayaj A.; Dholakia, Bhushan B.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2016)
Isoprenoids and phenylpropanoids are the major secondary metabolite constituents in Ocimum genus. Though enzymes from phenylpropanoid pathway have been characterized from few plants, limited information exists on how they modulate levels of secondary metabolites. Here, we performed phenylpropanoid profiling in different tissues from five Ocimum species, which revealed significant variations in secondary metabolites including eugenol, eugenol methyl ether, estragole and methyl cinnamate levels. Expression analysis of eugenol synthase (EGS) gene showed higher transcript levels especially in young leaves and inflorescence; and were positively correlated with eugenol contents. Additionally, transcript levels of coniferyl alcohol acyl transferase, a key enzyme diverting pool of substrate to phenylpropanoids, were in accordance with their abundance in respective species. In particular, eugenol methyl transferase expression positively correlated with higher levels of eugenol methyl ether in Ocimum tenuiflorum. Further, EGSs were functionally characterized from four Ocimum species varying in their eugenol contents. Kinetic and expression analyses indicated, higher enzyme turnover and transcripts levels, in species accumulating more eugenol. Moreover, biochemical and bioinformatics studies demonstrated that coniferyl acetate was the preferred substrate over coumaryl acetate when used, individually or together, in the enzyme assay. Overall, this study revealed the preliminary evidence for varied accumulation of eugenol and its abundance over chavicol in these Ocimum species. Current findings could potentially provide novel insights for metabolic modulations in medicinal and aromatic plants. (C) 2016 Elsevier B.V. All rights reserved.

Potential dual role of eugenol in inhibiting advanced glycation end products in diabetes: proteomic and mechanistic insights - Singh, Priyanka; Jayaramaiah, Ramesha H.; Agawane, Sachin B.; Vannuruswamy, Garikapati; Korwar, Arvind M.; Anand, Atul; Dhaygude, Vitthal S.; Shaikh, Mahemud L.; Joshi, Rakesh S.; Boppana, Ramanamurthy; Kulkarni, Mahesh J.; Thulasiram, Hirekodathakallu V.; et al. (Scientific Reports, 2016)
Medicinally important genus Ocimum harbors a vast pool of chemically diverse metabolites. Current study aims at identifying anti-diabetic candidate compounds from Ocimum species. Major metabolites in O. kilimandscharicum, O. tenuiflorum, O. gratissimum were purified, characterized and evaluated for anti-glycation activity. In vitro inhibition of advanced glycation end products (AGEs) by eugenol was found to be highest. Preliminary biophysical analysis and blind docking studies to understand eugenol-albumin interaction indicated eugenol to possess strong binding affinity for surface exposed lysines. However, binding of eugenol to bovine serum albumin (BSA) did not result in significant change in secondary structure of protein. In vivo diabetic mice model studies with eugenol showed reduction in blood glucose levels by 38% likely due to inhibition of alpha-glucosidase while insulin and glycated hemoglobin levels remain unchanged. Western blotting using anti-AGE antibody and mass spectrometry detected notably fewer AGE modified peptides upon eugenol treatment both in vivo and in vitro. Histopathological examination revealed comparatively lesser lesions in eugenol-treated mice. Thus, we propose eugenol has dual mode of action in combating diabetes; it lowers blood glucose by inhibiting a-glucosidase and prevents AGE formation by binding to epsilon-amine group on lysine, protecting it from glycation, offering potential use in diabetic management.

Sequence characterization and in silico structure prediction of fatty acid desaturases in linseed varieties with differential fatty acid composition - Rajwade, Ashwini V.; Joshi, Rakesh S.; Kadoo, Narendra Y.; Gupta, Vidya S. (Journal of the Science of Food and Agriculture, 2016)
BACKGROUND: Linseed is the richest agricultural source of alpha-linolenic acid (ALA), an omega-3 fatty acid (FA) that offers several nutritional benefits. In the present study, sequence characterization of six desaturase genes (SAD1, SAD2, FAD2, FAD2-2, FAD3A and FAD3B) and 3D structure prediction of their proteins from ten Indian linseed varieties differing in ALA content were performed to determine whether the nucleotide and amino acid (AA) sequence variants have any functional implications in differential accumulation of ALA or other FAs in linseed. RESULTS: The SAD and FAD2 genes exhibited few sequence variations among the ten varieties, forming only one or two protein isoforms. In contrast, the FAD3A and FAD3B genes showed more sequence variations and three or four protein isoforms. Interestingly, the two high-ALA varieties NL260 and Padmini had the same FAD3B nucleotide and protein isoforms, which differed from all other varieties. Surprisingly, no AA changes altered the 3D structures of the desaturase proteins. CONCLUSION: Several nucleotide and AA sequence variations in desaturase genes were observed; however, they did not alter the 3D structure of any desaturase protein and were not correlated with FA levels among the ten linseed varieties, which had different ALA contents. This suggests a complex regulatory process of biosynthesis of FAs in linseed. (C) 2016 Society of Chemical Industry

Improved tolerance against helicoverpa armigera in transgenic tomato over-expressing multi-domain proteinase inhibitor gene from capsicum annuum - Tanpure, Rahul S.; Barbole, Ranjit S.; Dawkar, Vishal V.; Waichal, Yashashree A.; Joshi, Rakesh S.; Giri, Ashok P.; Gupta, Vidya S. (Physiology and Molecular Biology of Plants, 2017)
Plant proteinase inhibitors (PIs) are plant defense proteins and considered as potential candidates for engineering plant resistances against herbivores. Capsicum annuum proteinase inhibitor (CanPI7) is a multi-domain potato type II inhibitor (Pin-II) containing four inhibitory repeat domains (IRD), which target major classes of digestive enzymes in the gut of Helicoverpa armigera larvae. Stable integration and expression of the transgene in T1 transgenic generation, were confirmed by established molecular techniques. Protein extract of transgenic tomato lines showed increased inhibitory activity against H. armigera gut proteinases, supporting those domains of CanPI7 protein to be effective and active. When T1 generation plants were analyzed, they exhibited antibiosis effect against first instar larvae of H. armigera. Further, larvae fed on transgenic tomato leaves showed delayed growth relative to larvae fed on control plants, but did not change mortality rates significantly. Thus, better crop protection can be achieved in transgenic tomato by overexpression of multi-domain proteinase inhibitor CanPI7 gene against H. armigera larvae.

Tripeptides derived from reactive centre loop of potato type II protease inhibitors preferentially inhibit midgut proteases of Helicoverpa armigera - Saikhedkar, Nidhi S.; Joshi, Rakesh S.; Bhoite, Ashwini S.; Mohandasan, Radhika; Yadav, Amit Kumar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2018)
Potato type II protease inhibitors (Pin-II PIs) impede the growth of lepidopteran insects by inhibiting serine protease-like enzymes in the larval gut. The three amino acid reactive centre loop (RCL) of these proteinaceous inhibitors is crucial for protease binding and is conserved across the Pin-II family. However, the molecular mechanism and inhibitory potential of the RCL tripeptides in isolation of the native protein has remained elusive. In this study, six peptides corresponding to the RCLs of the predominant Pin-II PIs were identified, synthesized and evaluated for in vitro and in vivo inhibitory activity against serine proteases of the polyphagous insect, Helicoverpa armigera. RCL peptides with sequences PRN, PRY and TRE were found to be potent inhibitors that adversely affected the growth and development of H. armigera. The binding mechanism and differential affinity of the RCL peptides with serine proteases was delineated by crystal structures of complexes of the RCL peptides with trypsin. Residues P1 and P2 of the inhibitors play a crucial role in the interaction and specificity of these inhibitors. Important features of RCL peptides like higher inhibition of insect proteases, enhanced efficacy at alkaline gut pH, longer retention and high stability in insect gut make them suitable molecules for the development of sustainable pest management strategies for crop protection.
Keywords: Helicoverpa armigera; Protease; protease inhibitor; Reactive centre loop peptides

Facilitator roles of viruses in enhanced insect resistance to biotic stress - Jagdale, Shounak S.; Joshi, Rakesh S. (Current Opinion in Insect Science, 2019)
Virus-insect interactions are primarily parasitic, yet diverse mutualistic interactions, some of which are symbiogenic, also occur. These viruses can modify insect physiology and behavior so that hosts can gain resistance against various biotic challenges like pathogen and parasites. In the recent past, many insect mutualistic viruses have been reported. Viruses can show symbiogenic interactions with some insects, which have been explored at the molecular level. However, understanding about molecular mechanisms for many of the mutualistic viruses is still enigmatic. Exploration of these interactions and its mechanism can shed light on phenomenon of virus mediated biotic stress resistance in insects.

NMR structure and dynamics of inhibitory repeat domain variant 12, a plant protease inhibitor from Capsicum annuum, and its structural relationship to other plant protease inhibitors - Gartia, Janeka; Anangi, Raveendra; Joshi, Rakesh S.; Giri, Ashok P.; King, Glenn F.; Barnwal, Ravi P.; Chary, Kandala V. R. (Journal of Biomolecular Structure & Dynamics, 2019)
Although several plant protease inhibitors have been structurally characterized using X-ray crystallography, very few have been studied using NMR techniques. Here, we report an NMR study of the solution structure and dynamics of an inhibitory repeat domain (IRD) variant 12 from the wound-inducible Pin-II type proteinase inhibitor from Capsicum annuum. IRD variant 12 (IRD12) showed strong anti-metabolic activity against the Lepidopteran insect pest, Helicoverpa armigera. The NMR-derived three-dimensional structure of IRD12 reveals a three-stranded anti-parallel beta-sheet rigidly held together by four disulfide bridges and shows structural homology with known IRDs. It is interesting to note that the IRD12 structure containing similar to 75% unstructured part still shows substantial amount of rigidity of N-H bond vectors with respect to its molecular motion. Communicated by Ramaswamy H. Sarma
Keywords: Bt transgenic; Capsicum annuum; Helicoverpa armigera; inhibitory repeating domains; NMR structure; Protease inhibitors (PIs)

Phyto-inspired cyclic peptides derived from plant Pin-II type protease inhibitor reactive center loops for crop protection from insect pests - Sailthedkar, Nidhi S.; Joshi, Rakesh S.; Yadav, Amit K.; Seal, Shubhendu; Fernandes, Moneesha; Giri, Ashok P. (Biochimica ET Biophysica Acta-General Subjects, 2019)
Background: Natural defence of plants against insect pests involves protease inhibitors (PIs) that interfere with insect digestive proteases. Pin-II type plant PIs are wound inducible upon insect damage and possess multiple inhibitory repeat domains that can inhibit trypsin and chymotrypsin-like proteases in the insect midgut. Yet, their agricultural ex-vivo application is limited due to large molecular size and environmental instability, which could be overcome by small peptides. Methods: Bicyclic peptides were designed by grafting Pin-II PIs derived reactive center loop (RCL) on synthetic tris(bromomethyl)benzene scaffold. In vitro binding with trypsin-like proteases was evaluated by biochemical and biophysical assays, followed by molecular dynamics simulations. In vivo effects on two major lepidopteran insect pests, Helicoverpa armigera and Spodoptera litura were studied upon feeding with peptide treated leaves. Affinity based pull down assays were used to identify target proteins in insect gut. Results: Bicyclic RCLs showed ten-fold enhanced protease inhibition compared to their linear counterparts. They exhibited feeding deterrence and growth reduction of lepidopteran insects. Bicyclic peptides predominantly interact with midgut serine proteases. Possible binding modes involve simultaneous interaction with the active site and specificity-determining residues of insect gut trypsin. Conclusion: Bicyclic peptides are potent inhibitors of serine proteases in the insect midgut. They cause feeding aversion and larval growth retardation. Bi-domain cyclic peptides interact with two sites on trypsin, leading to enhanced efficacy over linear RCL peptides. General significance: Bicyclic peptides mimic natural PIs by inhibiting insect proteases leading to growth reduction, thus, could be used as pest control molecules in agriculture.
Keywords: Cyclic peptide; Lepidoptera; Pest control; protease inhibitor; Reactive loop

Discovery of potential multi-target-directed ligands by targeting host-specific SARS-CoV-2 structurally conserved main protease - Joshi, Rakesh S.; Jagdale, Shounak S.; Bansode, Sneha B.; Shankar, S. Shiva; Tellis, Meenakshi B.; Pandya, Vaibhav Kumar; Chugh, Anita; Giri, Ashok P.; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in the current COVID-19 pandemic. Worldwide this disease has infected over 2.5 million individuals with a mortality rate ranging from 5 to 10%. There are several efforts going on in the drug discovery to control the SARS-CoV-2 viral infection. The main protease (M-Pro) plays a critical role in viral replication and maturation, thus can serve as the primary drug target. To understand the structural evolution of M-Pro, we have performed phylogenetic and Sequence Similarity Network analysis, that depicted divergence of Coronaviridae M-Pro in five clusters specific to viral hosts. This clustering was corroborated with the comparison of M-Pro structures. Furthermore, it has been observed that backbone and binding site conformations are conserved despite variation in some of the residues. These attributes can be exploited to repurpose available viral protease inhibitors against SARS-CoV-2 M-Pro. In agreement with this, we performed screening of similar to 7100 molecules including active ingredients present in the Ayurvedic anti-tussive medicines, anti-viral phytochemicals and synthetic anti-virals against SARS-CoV-2 M-Pro as the primary target. We identified several natural molecules like delta-viniferin, myricitrin, taiwanhomoflavone A, lactucopicrin 15-oxalate, nympholide A, afzelin, biorobin, hesperidin and phyllaemblicin B that strongly binds to SARS-CoV-2 M-Pro. Intrestingly, these molecules also showed strong binding with other potential targets of SARS-CoV-2 infection like viral receptor human angiotensin-converting enzyme 2 (hACE-2) and RNA dependent RNA polymerase (RdRp). We anticipate that our approach for identification of multi-target-directed ligand will provide new avenues for drug discovery against SARS-CoV-2 infection. Communicated by Ramaswamy H. Sarma
Keywords: Coronavirus; COVID-19; hACE-2; MPro; multi-target-directed ligand; protease inhibitor; RdRp; SARS-CoV-2 virus

Molecular determinant for specificity: differential interaction of alpha-amylases with their proteinaceous inhibitors - Rane, Ashwini S.; Joshi, Rakesh S.; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2020)
Background: alpha-Amylase inhibitors (alpha-AIs) belong to the discrete classes, and exhibited differential specificities against alpha-amylases from various sources. Several alpha-amylases and their complexes with inhibitors at the molecular level have been studied in detail. Interestingly, some alpha-AIs depict specific and selective interactions amid different insect alpha-amylases. Scope of review: There are studies to understand evolutionary variability and functional differentiation of insect alpha-amylases and their cognate inhibitors. We have examined sequence, structural, and interaction diversity between various alpha-amylases and alpha-AIs. Based on these analyses, we are providing a potential basis for the functional differentiation among certain insect a-amylases concerning mammalian counterparts and their interactions with different proteinaceous alpha-AIs. Major conclusions: Insect alpha-amylases have conserved domain architecture with differences in length, number of disulfide bonds, and secondary structure. Furthermore, few of them exhibit variable characteristics like chloride dependent activity, the presence of N-terminal glutamine residue to protect against proteolytic degradation, and loop variations near the enzyme active site. Conformation of alpha-AI protein could be an essential factor for their specificity and binding affinities towards target alpha-amylase(s). Furthermore, variation into the enzyme binding pocket residues might contribute to differential interactions with inhibitors. General significance: Molecular insights in the interactions between insect alpha-amylases and plant alpha-AI will provide the details of mechanisms assisting the inhibitor specificity. Furthermore, this information will help to design potent and effective alpha-AIs against specific alpha-amylase.
Keywords: Active site; alpha-amylase; alpha-amylase inhibitor; Insect; molecular interactions

Molecular investigation of coleopteran specific alpha-amylase inhibitors from amaranthaceae members - Rane, Ashwini S.; Venkatesh, Varun; Joshi, Rakesh S.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2020)
alpha-Amylase inhibitors (alpha-AIs) target alpha-amylases and interfere with the carbohydrate digestion of insects. Among different classes of alpha-AIs, a knottin-type inhibitor from Amaranthus hypochondriacus (AhAI) was found to be specific against coleopteran storage pests. In this report, we have characterized three previously unidentified knottin-type alpha-AIs from various Amaranthaceae plants namely, Amaranthus hypochondriacus (AhAI2), Alternanthera sessilis (AsAI) and Chenopodium quinoa (CqAI). They contain a signal peptide, pro-peptide, and mature peptide. The mature peptides of the new alpha-AIs shared 68 to 78% identity with AhAI and have highly variable pro-peptide regions. Along with the cystine-knot fold, they showed conservation of reactive site residues. All recombinant alpha-AIs were successfully expressed in their active form and native state using an oxidative cytoplasmic environment. Inhibition studies against various amylases revealed that these inhibitors showed selective inhibition of coleopteran recombinant insect alpha-amylases viz., Tribolium castaneum, and Callosobruchus chinensis. Tribolium castaneum alpha-amylase inhibition potency was highest for AhAI2 (Ki similar to 15 mu M) followed by AsAI (Ki similar to 43 mu M) and CqAI (Ki similar to 61 mu M). Interaction analysis of these inhibitors illustrated that the reactive site of inhibitors make several non-covalent interactions with the substrate-binding pocket of coleopteran alpha-amylases. The selectivity of these inhibitors against coleopteran a-amylases highlights their potential in storage grain pest control. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: alpha-amylase; alpha-amylase inhibitor; Amaranthaceae; Coleoptera; Knottin-type

Possible role of glycation in the regulation of amyloid beta precursor protein processing leading to amyloid beta accumulation - Patil, Gouri V.; Joshi, Rakesh S.; Kazi, Rubina S.; Kulsange, Shabda E.; Kulkarni, Mahesh J. (Medical Hypotheses, 2020)
Alzheimer's disease (AD) is one of the most common forms of neurodegenerative diseases amongst the aged population. The disease is multifactorial, and diabetes has been considered as one of the major risk factors for the development of AD. Chronic hyperglycemic condition in diabetes promotes non-enzymatic protein modification by glucose termed as glycation, which affects protein structure and function. Previous studies have shown that many of the enzymes, including proteases, are affected by glycation. Conversely, glycated proteins are known to become resistant to protease action. In these hypotheses, we have extended these two concepts to the regulation of amyloid-beta protein precursor (A beta PP) by secretases leading to amyloid-beta (Af3) accumulation. The first hypothesis deals with the glycation of alpha-secretases leading to its reduced activity, while in the second hypothesis, A beta PP glycation may prevent a-secretases action, rendering its processing by beta secretase. As diabetes is a risk factor for the development of AD, either or both these pathways may operate, leading to the manifestation of AD.
Keywords: Alpha-secretase; Alzheimer `s disease; Amyloid-beta; Amyloid-beta protein precursor; Beta-secretase; Diabetes; glucose; Glycation; Type-3 diabetes

Antiviral drugs prioritization for COVID-19 management based on rational selection - Joshi, Rakesh S.; Giri, Ashok P.; Kulkarni, Mahesh J.; Gupta, Mahesh; Verma, Savita; Chaudhry, Dhruva; Deshmukh, Narendra; Chugh, Anita (Current Science, 2021)
The SARS-CoV-2 infection has resulted in COVID-19 pandemic worldwide. It has infected around 0.1 billion individuals and caused 2 million fatalities across the globe till mid-January 2021. Drug repurposing has been utilized as the most preferred therapeutic intervention for COVID-19 mitigation due to its necessity and feasibility. To prioritize therapeutic regime against COVID-19, we used 61 antiviral drugs and their combinations. Selected molecules were subjected to virtual screening against: (i) human angiotensin-converting enzyme 2 receptor binding domain (hACE-2) which serves as an anchor for virus attachment and entry, (ii) SARS-CoV-2 RNA dependent RNA polymerase (RdRp) responsible for viral RNA replication, and (iii) SARS-CoV-2 main protease (M-Pro) needed for viral polyprotein slab proteolytic processing. Based on docking score, pharmacodynamic and pharmacokinetic parameters, combinations of Daclatasvir, Elbasvir, Indinavir, Ledipasvir, Paritaprevir and Rilpivirine were analysed further. Our analysis suggested Sofosbuvir in combination with Ledipasvir and Daclatasvir as potential therapeutic agents for SARS-CoV-2. The combined score suggests that these combinations have superior anti-SARS-CoV-2 potential than Remdesivir and other investigational drugs. The present work provides a rationale-based approach to select drugs with possible anti-SARS-CoV-2 activity for further clinical evaluation.
Keywords: Drug repurposing; hACE-2; main protease; RNA dependent RNA polymerase; SARS-CoV-2

Functional insights into two Ocimum kilimandscharicum 4-coumarate-CoA ligases involved in phenylpropanoid biosynthesis - Lavhale, Santosh G.; Joshi, Rakesh S.; Kumar, Yashwant; Giri, Ashok P. (International Journal of Biological Macromolecules, 2021)
Plant 4-coumarate-CoA ligase (4CL) catalyzes the ligation of CoA to cinnamic acid and its derivatives. Activated CoA esters are utilized for the biosynthesis of phenolic metabolites and lignin that play essential function in plants. Here, we characterize the diversity of Ocimum kilimandscharicum 4CLs (Ok4CLs). Phylogenetic analysis suggest that Ok4CLs could be grouped into three classes, class I -enzymes mostly involved in lignin biosynthesis, class II -non-structural phenylpropanoid biosynthesis and class III -yet to be characterized for specific role(s). We selected two Ok4CLs namely Ok4CL7 and Ok4CL15 for further characterization. Gene expression analysis sug-gested that Ok4CL7 is highly expressed in leaf trichomes, whereas Ok4CL15 is abundant in the roots. The recom-binant Ok4CL7 and Ok4CL15 had optimal enzyme activities at 40 degrees C in pH 8 and 7, respectively. Ok4CL7 showed substrate preference towards p-coumaric acid, ferulic acid and caffeic acid. While, Ok4CL15 preferredp-coumaric acid, ferulic acid and sinapic acid. Feruloyl adenylate showed higher number of contacts and lowers binding en-ergy with Ok4CL7 and 15 compared to cinnamoyl adenylate. Based on root-specific expression and preference for sinapic acid, Ok4CL15 might be involved in lignin biosynthesis. Further exploration is needed to unravel the role of diverse Ok4CLs in O. kilimandscharicum. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: 4-Coumarate-CoA ligase; Flavonoids; lignin; Ocimum kilimandscharicum; Phenylpropanoids

Glucosinolate induces transcriptomic and metabolic reprogramming in Helicoverpa armigera - Jagdale, Shounak; Tellis, Meenakshi; Barvkar, Vitthal T.; Joshi, Rakesh S. (3 Biotech, 2021)
Glucosinolates protect plants from herbivory. Lepidopteran insects have developed resistance to glucosinolates which is well studied. However, the molecular effects of glucosinolate intake on insects are unexplored. To elucidate this, we performed transcriptomics and metabolomics of sinigrin-fed Helicoverpa armigera. Transcriptomics exhibits significant dysregulation of 2375 transcripts, of which 1575 are upregulated and 800 downregulated. Gene Ontology analysis of differentially expressed genes reveals that key hydrolases, oxidoreductases, and transferases are majorly affected. The negative impact of sinigrin is significant and localized in the endomembrane system and mitochondria. It also disturbs various biological processes such as regulation of protein metabolism and cytoskeletal organization. Furthermore, H. armigera putative myrosinase-like enzymes may catalyze the breakdown of sinigrin to allyl isothiocyanate (AITC). AITC targets the electron transport chain causing oxidative stress. KEGG pathway enrichment shows significant upregulation of oxidative phosphorylation, glutathione metabolism and amino acid metabolism. Activation of these pathways induces glutathione synthesis for sinigrin detoxification. Differential gene expression indicates upregulation of glutathione S-transferase and succinate dehydrogenase suggesting mitochondrial impact. Transcriptomics data correlated with metabolomics show changes in serine, methionine, ornithine, and other metabolite levels. It corroborates well with the transcript alterations supporting the increased glutathione production. Thus, our data suggest that sinigrin generates oxidative stress in H. armigera and insects alter their metabolic wiring to overcome sinigrin-mediated deleterious effects.
Keywords: Detoxification; Glucosinolate; Glutathione; mitochondria; Oxidative stress

Molecular characterization of the beta(2)-like octopamine receptor of helicoverpa armigera - Gujar, Nidhi; Nikte, V, Siddhanta; Joshi, Rakesh S.; Joshi, Manali (Journal of Membrane Biology, 2021)
Helicoverpa armigera is a devastating polyphagous and cosmopolitan crop pest. There are reports of this insect being resistant to a variety of pesticides raising concern worldwide. The Octopamine (OA) binding beta(2)-like receptor (OAR), a GPCR, is widely distributed in the nervous system of the insect and plays essential roles in the physiology and development and thus is an important target for insecticides. Yet, the molecular characterization of the H. armigera OAR (HarmOAR) and rational design of compounds based on this receptor is lacking. As a first step, we performed multiple sequence alignment of all insect OARs, which revealed that the sequences contained all conserved class A GPCR motifs. Phylogenetic studies showed clade-specific variations in the protein sequences primarily arising owing to differences in the ICL3 loop region. Further, a structural model of HarmOAR was built using the inactive human beta(2)AR as a template. 0.9 mu s atomistic simulations revealed conserved inter helical contacts and water molecules of HarmOAR. The detailed binding of octopamine was studied using molecular docking and 0.3 mu s atomistic simulations. Twenty-two insecticides active against octopamine receptors of other insects were compiled and docked to HarmOAR followed by rescoring with binding free energies to prioritize them for H. armigera. Our study suggests alpha-terpineol to be a good candidate as an insecticide or insect repellent for Helicoverpa armigera.
Keywords: docking; Helicoverpa armigera; Insecticides; molecular dynamics; Octopamine receptor; Phylogeny

Molecular investigation of glycated insulin-induced insulin resistance via insulin signaling and AGE-RAGE axis - Walke, Prachi B.; Bansode, Sneha B.; More, Nikita P.; Chaurasiya, Arvindkumar H.; Joshi, Rakesh S.; Kulkarni, Mahesh J. (Biochimica ET Biophysica Acta-Molecular Basis of Disease, 2021)
Hyperglycemic condition in diabetes promotes glycation of various plasma proteins including insulin. Glycation of insulin has been reported to reduce its biological activity. Reduced biological activity of glycated insulin could be either due to reduced affinity for the insulin receptor and impaired insulin signaling, or it can act as a ligand for the receptor for advanced glycation end products (RAGE) and activates oxidative stress and pro-inflammatory pathways leading to insulin resistance. This study investigates the effect of glycated insulin on both insulin and RAGE signaling. Glycated insulin treatment to Chinese hamster ovary (CHO-IR-GLUT4) cells stably expressing insulin receptor (IR) and glucose transporter fused with a green fluorescent protein (GLUT4-GFP) resulted in the impairment of insulin signaling, as the phosphorylation of IR and AKT significantly reduced, which affected GLUT4 translocation and glucose uptake. Moreover, it also activated RAGE signaling as observed by increased expression of NADPH oxidase accompanied by an increase in reactive oxygen species (ROS). Immunofluorescence study indicated the translocation of NF-kappa B to the nucleus upon treatment of glycated insulin. This was associated with increased RAGE expression, Caspase 3, and cell death. Downregulation of RAGE with the losartan treatment restored the impaired insulin signaling and glucose uptake. Additionally, in silico study demonstrated that glycated insulin has reduced binding affinity to insulin receptor and increased binding affinity to RAGE. Overall, this study demonstrates the role of glycated insulin in exacerbating insulin resistance by impairing insulin signaling as well as stimulating AGE-RAGE signaling.
Keywords: AGE; Diabetes; Glycation; Hyperglycemia; insulin; RAGE

Repurposing the McoTI-II rigid molecular scaffold in to inhibitor of `papain superfamily' cysteine proteases - Mishra, Manasi; Singh, Vigyasa; Tellis, Meenakshi B.; Joshi, Rakesh S.; Singh, Shailja (Pharmaceuticals, 2021)
Clan C1A or `papain superfamily' cysteine proteases are key players in many important physiological processes and diseases in most living systems. Novel approaches towards the development of their inhibitors can open new avenues in translational medicine. Here, we report a novel design of a re-engineered chimera inhibitor Mco-cysteine protease inhibitor (CPI) to inhibit the activity of C1A cysteine proteases. This was accomplished by grafting the cystatin first hairpin loop conserved motif (QVVAG) onto loop 1 of the ultrastable cyclic peptide scaffold McoTI-II. The recombinantly expressed Mco-CPI protein was able to bind with micromolar affinity to papain and showed remarkable thermostability owing to the formation of multi-disulphide bonds. Using an in silico approach based on homology modelling, protein-protein docking, the calculation of the free-energy of binding, the mechanism of inhibition of Mco-CPI against representative C1A cysteine proteases (papain and cathepsin L) was validated. Furthermore, molecular dynamics simulation of the Mco-CPI-papain complex validated the interaction as stable. To conclude, in this McoTI-II analogue, the specificity had been successfully redirected towards C1A cysteine proteases while retaining the moderate affinity. The outcomes of this study pave the way for further modifications of the Mco-CPI design for realizing its full potential in therapeutics. This study also demonstrates the relevance of ultrastable peptide-based scaffolds for the development of novel inhibitors via grafting.
Keywords: Cathepsin; Clan CA cysteine proteases; cyclotide; cystatin; McoTI-II; papain; protein engineering

Cyclic peptide engineered from phytocystatin inhibitory hairpin loop as an effective modulator of falcipains and potent antimalarial - Mishra, Manasi; Singh, Vigyasa; Tellis, Meenakshi B.; Joshi, Rakesh S.; Pandey, Kailash C.; Singh, Shailja (Journal of Biomolecular Structure & Dynamics, 2022)
Cystatins are classical competitive inhibitors of C1 family cysteine proteases (papain family). Phytocystatin superfamily shares high sequence homology and typical tertiary structure with conserved glutamine-valine-glycine (Q-X-V-X-G) loop blocking the active site of C1 proteases. Here, we develop a cysteine-bounded cyclic peptide (CYS-cIHL) and linear peptide (CYS-IHL), using the conserved inhibitory hairpin loop amino acid sequence. Using an in silico approach based on modeling, protein-peptide docking, molecular dynamics simulations and calculation of free energy of binding, we designed and validated inhibitory peptides against falcipain-2 (FP-2) and -3 (FP-3), cysteine proteases from the malarial parasite Plasmodium falciparum. Falcipains are critical hemoglobinases of P. falciparum that are validated targets for the development of antimalarial therapies. CYS-cIHL was able to bind with micromolar affinity to FP-2 and modulate its binding with its substrate, hemoglobin in in vitro and in vivo assays. CYS-cIHL could effectively block parasite growth and displayed antimalarial activity in culture assays with no cytotoxicity towards human cells. These results indicated that cyclization can substantially increase the peptide affinity to the target. Furthermore, this can be applied as an effective strategy for engineering peptide inhibitory potency against proteases.
Keywords: Cyclic peptide; falcipain inhibitors; falciparum; P; Phytocystatin; protein interaction mimics; protein&#8211

Functional diversity of the lepidopteran ATP-binding cassette transporters - Barve, Pranoti R.; Tellis, Meenakshi B.; Barvkar, Vitthal T.; Joshi, Rakesh S.; Giri, Ashok P.; Kotkar, Hemlata M. (Journal of Molecular Evolution, 2022)
The ATP-binding cassette (ABC) transporter gene family is ubiquitous in the living world. ABC proteins bind and hydrolyze ATP to transport a myriad of molecules across various lipid-containing membrane systems. They have been studied well in plants for transport of a variety of compounds and particularly, in vertebrates due to their direct involvement in resistance mechanisms against several toxic molecules/metabolites. ABC transporters in insects are found within large multigene families involved in the efflux of chemical insecticides and toxic/undesired metabolites originating from food and endogenous metabolism. This review deals with ABC transporter subfamilies of few agronomically important Lepidopteran pests. The transcriptional dynamics and regulation of ABC transporters during insect development emphasizes their functional diversity against insecticides, Cry toxins, and plant specialized metabolites. To generate insights about molecular function and physiological roles of ABCs, functional and structural characterization is necessary. Also, expansion and divergence of ABC transporter gene subfamilies in Lepidopteran insects needs more systematic investigation. We anticipate that newer methods of insect control in agriculture can benefit from an understanding of ABC transporter interactions with a vast range of natural specialized molecules and synthetic compounds.
Keywords: ABC transporters; Bt; insecticide resistance; Lepidoptera; Plant metabolites

Developing a feeding assay system for evaluating the insecticidal effect of phytochemicals on Helicoverpa armigera - Mohite, Sharada D.; Patil, Yogita P.; Nichit, Vikram J.; Joshi, Rakesh S. (Jove-Journal of Visualized Experiments, 2023)
Helicoverpa armigera, a lepidopteran insect, is a polyphagous pest with a worldwide distribution. This herbivorous insect is a threat to plants and agricultural productivity. In response, plants produce several phytochemicals that negatively impact the insect's growth and survival. This protocol demonstrates an obligate feeding assay method to evaluate the effect of a phytochemical (quercetin) on insect growth, development, and survival. Under controlled conditions, the neonates were maintained until the second instar on a pre-defined artificial diet. These second-instar larvae were allowed to feed on a control and quercetin-containing artificial diet for 10 days. The insects' body weight, developmental stage, frass weight, and mortality were recorded on alternate days. The change in body weight, the difference in feeding pattern, and developmental phenotypes were evaluated throughout the assay time. The described obligatory feeding assay simulates a natural mode of ingestion and can be scaled up to a large number of insects. It permits one to analyze phytochemicals' effect on the growth dynamics, developmental transition, and overall fitness of H. armigera. Furthermore, this setup can also be utilized to evaluate alterations in nutritional parameters and digestive physiology processes. This article provides a detailed methodology for feeding assay systems, which may have applications in toxicological studies, insecticidal molecule screening, and understanding chemical effects in plant-insect interactions.

Domain shuffling and site-saturation mutagenesis for the enhanced inhibitory potential of amaranthaceae α-amylase inhibitors - Rane, Ashwini S.; Nair, Vineetkumar S.; Joshi, Rakesh S.; Giri, Ashok P. (Protein Journal, 2023)
Amaranthaceae a-amylase inhibitors (AAIs) are knottin-type proteins with selective inhibitory potential against coleopteran a-amylases. Their small size and remarkable stability make them exciting molecules for protein engineering to achieve superior selectivity and efficacy. In this report, we have designed a set of AAI pro- and mature peptides chimeras. Based on in silico analysis, stable AAI chimeras having a stronger affinity with target amylases were selected for characterization. In vitro studies validated that chimera of the propeptide from Chenopodium quinoa a-AI and mature peptide from Beta vulgaris a-AI possess 3, 7.6, and 4.26 fold higher inhibition potential than parental counterparts. Importantly, recombinant AAI chimera retained specificity towards target coleopteran a-amylases. In addition, to improve the inhibitory potential of AAI, we performed in silico site-saturation mutagenesis. Computational analysis followed by experimental data showed that substituting Asparagine at the 6th position with Methionine had a remarkable increase in the specific inhibition potential of Amaranthus hypochondriacus a-AI. These results provide structural-functional insights into the vitality of AAI propeptide and a potential hotspot for mutagenesis to enhance the AAI activity. Our investigation will be a toolkit for AAI's optimization and functional differentiation for future biotechnological applications.
Keywords: & alpha; -Amylase; -Amylase inhibitors; Amaranthaceae; Coleoptera; Peptide; Pest control

Regulation of trehalose metabolism in insects: from genes to the metabolite window - Tellis, Meenakshi B.; Kotkar, Hemlata M.; Joshi, Rakesh S. (Glycobiology, 2023)
Trehalose is a major circulatory sugar in the haemolymph of insects. It provides instant energy and protection against stress. Trehalose metabolism is associated with insect growth and development. The architecture and spatio-temporal expression dynamics of trehalose metabolism and transport genes are key for regulation. These genes are controlled by various transcription factors, largely linked to nutrition, insect development, and metamorphosis. Also, trehalose levels are affected by substrate affinities and modifications of enzymes involved in the pathway. A feedback mechanism involving the precursors and products can regulate trehalose metabolism. Further, the neuroendocrine system controls trehalose levels under normal and stressed conditions by producing different hormones. Hypotrehalosemic hormones work under surplus energy conditions to activate haemolymph trehalose uptake and degradation. In contrast, hypertrehalosemic hormones stimulate trehalose production in the fat body and its transport to the haemolymph. However, trehalose metabolism regulation in insects needs to be studied in detail. This review discusses aspects of trehalose synthesis, transport, and degradation dynamics in developmental transition and stress response. Unraveling the epigenetic factors, transcriptional control and chemical or genetic modulators can provide further insights into the intricate regulation of trehalose in a development- and tissue-specific manner. This molecular information about effectors and regulators of trehalose metabolism can be applied in developing diverse biotechnological applications.
Keywords: Hormone; Insect development; Metabolic regulation; Stress; trehalose

Trehalose transporter-like gene diversity and dynamics enhances stress response and recovery in Helicoverpa armigera - Tellis, Meenakshi B.; Chaudhari, Bhagyashri Y.; Deshpande, Shweta V.; Nikam, Sanika V.; Barvkar, Vitthal T.; Kotkar, Hemlata M.; Joshi, Rakesh S. (Gene, 2023)
Trehalose is a primary sugar and its distribution across the insect body, regulated by trehalose transporters (TRETs), is essential for sugar metabolism and energy homeostasis. The large diversity of Tret-like sugar trans-porters (ST), belonging to SLC2A transporter family, in polyphagous insects probably contributes to their extremely adaptive nature. We aim to study spatio-temporal expression dynamics and functional relevance of ST transcript variants in the lepidopteran model organism, Helicoverpa armigera. Identification of 69 putative Tret-like HaST transcript variants from databases and their digital gene expression analysis indicated tissue and development-specific expression patterns. Phylogenetic and sequence similarity network analysis of HaSTs signify evolutionary divergence, while motif and structure analysis depicted conserved signatures. In vitro gene expression validation for selected genes depicts that HaST09 and 69 are fat body and haemolymph-specific. While, HaST06, 30, 36 and 57 are developmental stage or sex-specific. HaST69 has high expression in the haemolymph of fifth instar larvae. In the presence of trehalose metabolism inhibitors and abiotic stress, HaSTs expression show dysregulation, indicating their possible association with trehalose metabolism and stress re-covery. In vivo gene silencing of HaST69 resulted in reduced trehalose accumulation in the insect body, sug-gesting its plausible role in sugar metabolism. The overall understanding of HaST diversity and expression dynamics highlights their putative roles in sugar transport during adaptation and stress recovery of insects.
Keywords: Gene expression; Helicoverpa armigera; Stress; Transporter-like; trehalose

Adsorption based downstream processing approach for penicillin V from a Penicillium chrysogenum BIONCL I22 culture filtrate - Mishal, Bela H.; Das, Sancharini; Mahajan, Vaishnavi N.; Dharne, Mahesh S.; Joshi, Rakesh S.; Giri, Ashok P. (ACS Omega, 2024)
Penicillin V (phenoxy methyl penicillin) is highly sought after among natural penicillins because of its exceptional acid stability and effectiveness against common skin and respiratory infections. Given its wide-ranging therapeutic uses, there is a need to establish a greener method for its maximum recovery to reduce the carbon footprint. Here, we have identified and validated optimized operational conditions for resin-based penicillin V recovery. It was observed that Amberlite XAD4 had the highest penicillin V hydrophobic adsorption capacity among the other screened resins. Kinetic and isothermal studies using linear and nonlinear regression analysis showed that the adsorption process well fitted with pseudo-second-order kinetics (R-2 = 0.9816) and the Freundlich adsorption isotherm model (R-2 = 0.9871). Adsorption equilibrium was attained within 4 h, while maximum adsorption was observed at 3 mg/mL penicillin V concentration. Furthermore, the optimized extraction protocol was compared with the conventional butyl acetate-based downstream processing. Under optimum conditions resin-based penicillin V recovery was 2-fold higher as compared to the solvent extraction method and the resin could be reused for over six cycles without compromising the yield. These findings signify substantial progress toward the development of an environmentally sustainable approach for penicillin V recovery and a potentially viable method for extractive fermentation.

Aroma Alchemy: uridine diphosphate-dependent glycosyltransferases mediated regulation of fruit aroma and flavor biosynthesis - Vare, Tejas B.; Joshi, Rakesh S.; Giri, Ashok P. (Phytochemistry Reviews, 2024)
The aroma compounds contribute to fruits flavor, taste, and nutritional value. These compounds include various chemical classes such as terpenoids, lactones, ketones, esters, acids, alcohols, and their derivatives. Uridine diphosphate-dependent glycosyltransferases (UGTs) modify these compounds by covalently adding one or multiple sugar molecules. This glycosylation process converts volatile, unstable, and hydrophobic aroma compounds into hydrophilic, stable, and slow-releasing reservoirs of fruit flavor. The diversity and spatio-temporal expression patterns of UGTs play a crucial role in forming a wide range of glycosylated aroma compounds. This review focuses on aroma-related compounds in both free and glycosylated-bound forms found in commercial vital fruits. We discuss various fruit-specific UGTs and their role in the glycosylation of aroma compounds. Based on structural and functional information on UGTs, we have assessed sugar donor specificity and the residues responsible for the same. Moreover, phylogenetic analysis of characterized UGTs provides insights into their substrate preferences. We also surveyed the expression dynamics of UGTs during fruit ripening, as the switching between aglycon and glycosylated-bound forms of aroma compounds significantly impacts fruit quality. Potential applications of UGTs in the food and fragrance industry have been discussed. The information reviewed could be beneficial for developing novel methods for flavor manipulation of commercially important glycosides derived from natural resources.
Keywords: Aroma; Flavor; Fruit; Glycoconjugates; Glycosyltransferase; Volatile compounds

Article chitinase inhibition induces transcriptional dysregulation altering ecdysteroid-mediated control of spodoptera frugiperda development - Barbole, Ranjit S.; Sharma, Shivani; Patil, Yogita; Giri, Ashok P.; Joshi, Rakesh S. (Iscience, 2024)
Chitinases and ecdysteroid hormones are vital for insect development. Crosstalk between chitin and ecdysteroid metabolism regulation is enigmatic. Here, we examined chitinase inhibition effect on Spodopsilencing and overexpression resulted in ecdysone receptor deregulation. Transcription factors, like Neverland, and other ecdysteroid biosynthesis genes might lead to their upregulation in berberine-fed chitinase activity's impact on ecdysone biosynthesis and its transcriptional crosstalk.

Engineering inhibitory repeat domains of Pin-II type proteinase inhibitors indicate their high structural-functional tolerance to mutagenesis - Barbole, Ranjit S.; Joshi, Rakesh S.; Giri, Ashok P. (Biochemical and Biophysical Research Communications, 2024)
Plant proteinase inhibitors (PIs) are critical in defending against biotic stress. Most PIs contain an inhibitory repeat domain (IRD), which serves as the functional component, displaying a high degree of sequence and structural conservation. In this study, we examined the structural and functional resilience of IRDs using a combination of computational modeling and experimental validation. We have taken an evolution-based approach to enhance the PIs effectiveness of two previously identified Capsicum annuum IRDs, IRD4 and IRD10. Through in silico site-saturation mutagenesis of IRD4 and IRD10, we identified key sites associated with enhanced PI activity for targeted mutagenesis. Binding energy predictions for a mutant IRD library, tested against target proteases, suggested that positions R11 and N32 in IRD4 and N32 and H33 in IRD10 were promising candidates for further modification to improve inhibitory potential. Subsequent experimental validation revealed that the mutant proteins IRD4_R11K and IRD4_N32S exhibited stronger chymotrypsin inhibition than the wild-type (WT) IRD4. Similarly, the mutants IRD10_N32S and IRD10_H33 N demonstrated improved trypsin inhibition relative to the WT IRD10. These findings indicate that engineered IRD variants can tolerate structural changes while maintaining or enhancing their inhibitory activity against target proteases. Overall, this study demonstrates the potential of engineering PIs to increase their structural and functional resilience, offering new opportunities for biotechnological applications.
Keywords: Capsicum annum; Inhibitory repeat domain; molecular modeling; plant proteinase inhibitors; Proteases; Saturation mutagenesis

Inhibition of trehalose synthesis in lepidoptera reduces larval fitness - Tellis, Meenakshi B.; Mohite, Sharada D.; Nair, Vineetkumar S.; Chaudhari, Bhagyashri Y.; Ahmed, Shadab; Kotkar, Hemlata M.; Joshi, Rakesh S. (Advanced Biology, 2024)
Trehalose is synthesized in insects through the trehalose 6-phosphate synthase and phosphatase (TPS/TPP) pathway. TPP dephosphorylates trehalose 6-phosphate to release trehalose. Trehalose is involved in metamorphosis, but its relation with body weight, size, and developmental timing is unexplored. The expression and activity of TPS/TPP fluctuate depending on trehalose demand. Thus, TPS/TPP inhibition can highlight the significance of trehalose in insect physiology. TPS/TPP transcript levels are elevated in the pre-pupal and pupal stages in Helicoverpa armigera. The inhibition of recombinantly expressed TPP by N-(phenylthio)phthalimide (NPP), is validated by in vitro assays. In vivo inhibition of trehalose synthesis reduces larval weight and size, hampers metamorphosis, and reduces its overall fitness. Insufficient trehalose leads to a shift in glucose flux, reduced energy, and dysregulated fatty acid oxidation. Metabolomics reaffirms the depletion of trehalose, glucose, glucose 6-phosphate, and suppressed tricarboxylic acid cycle. Reduced trehalose hampers the energy level affecting larval vitality. Through trehalose synthesis inhibition, the importance of trehalose in insect physiology and development is investigated. Also, in two other lepidopterans, TPP inhibition impedes physiology and survival. NPP is also found to be effective as an insecticidal formulation. Overall, trehalose levels affect the larval size, weight, and metabolic homeostasis for larval-pupal transition in lepidoptera. Inhibition of trehalose synthesis enzyme TPS/TPP is a good model to study the contribution of trehalose in attaining body weight and in larval-pupal transition. Transcriptomics and metabolomics studies reveal overall reduced energy and dysregulated glucose, protein, and fatty acid metabolism.image
Keywords: Lepidoptera; metabolic homeostasis; trehalose; trehalose 6-phosphate phosphatase

Ocimum kilimandscharicum 4CL11 negatively regulates adventitious root development via accumulation of flavonoid glycosides - Lavhale, Santosh G.; Kondhare, Kirtikumar R.; Sinthadurai, Veenothini S.; Barvkar, Vitthal T.; Kale, Rutuja S.; Joshi, Rakesh S.; Giri, Ashok P. (Plant Journal, 2024)
4-Coumarate-CoA Ligase (4CL) is an important enzyme in the phenylpropanoid biosynthesis pathway. Multiple 4CLs are identified in Ocimum species; however, their in planta functions remain enigmatic. In this study, we independently overexpressed three Ok4CL isoforms from Ocimum kilimandscharicum (Ok4CL7, -11, and -15) in Nicotiana benthamiana. Interestingly, Ok4CL11 overexpression (OE) caused a rootless or reduced root growth phenotype, whereas overexpression of Ok4CL15 produced normal adventitious root (AR) growth. Ok4CL11 overexpression in N. benthamiana resulted in upregulation of genes involved in flavonoid biosynthesis and associated glycosyltransferases accompanied by accumulation of specific flavonoid-glycosides (kaempferol-3-rhamnoside, kaempferol-3,7-O-bis-alpha-l-rhamnoside [K3,7R], and quercetin-3-O-rutinoside) that possibly reduced auxin levels in plants, and such effects were not seen for Ok4CL7 and -15. Docking analysis suggested that auxin transporters (PINs/LAXs) have higher binding affinity to these specific flavonoid-glycosides, and thus could disrupt auxin transport/signaling, which cumulatively resulted in a rootless phenotype. Reduced auxin levels, increased K3,7R in the middle and basal stem sections, and grafting experiments (intra and inter-species) indicated a disruption of auxin transport by K3,7R and its negative effect on AR development. Supplementation of flavonoids and the specific glycosides accumulated by Ok4CL11-OE to the wild-type N. benthamiana explants delayed the AR emergence and also inhibited AR growth. While overexpression of all three Ok4CLs increased lignin accumulation, flavonoids, and their specific glycosides were accumulated only in Ok4CL11-OE lines. In summary, our study reveals unique indirect function of Ok4CL11 to increase specific flavonoids and their glycosides, which are negative regulators of root growth, likely involved in inhibition of auxin transport and signaling.
Keywords: 4-Coumarate-CoA ligase; 7-O-bis-alpha-l-rhamnoside; adventitious root; auxin transport; Flavonoids; kaempferol-3; Ocimum kilimandscharicum; quercetin-3-O-rutinoside; rootless

Tyramine-mediated hyperactivity modulates the dietary habits in Helicoverpa armigera - Patil, Yogita P.; Gawari, Shyam K.; Barvkar, Vitthal T.; Joshi, Rakesh S. (JOURNAL OF CHEMICAL ECOLOGY, 2024)
Keywords: amines; Behavior; dopamine; octopamine; RECEPTOR; sensitivity; SULFAKININ

Altered Octopamine synthesis impairs tyrosine metabolism affecting Helicoverpa armigera vitality - Patil, Yogita P.; Wagh, Deepti S.; Barvkar, Vitthal T.; Gawari, Shyam K.; Pisalwar, Priyanka D.; Ahmed, Shadab; Joshi, Rakesh S. (Pesticide Biochemistry and Physiology, 2025)
Tyramine (1-hydroxylase (T(1H) is a key enzyme in the biosynthesis of octopamine (OA), a vital neurohormone in invertebrates. This study explores the expression patterns and functional role of Helicoverpa armigera T(1H (HaT(1H) across various tissues and developmental stages. HaT(1H expression was highest in the head and adult male stages, reflecting tissue-specific and developmental regulation. HaT(1H silencing significantly increased locomotion and decreased feeding behavior. OA supplementation in silenced insects or HaT(1H overexpression showed a contrary effect on locomotory and feeding behavior. In silico screening and inhibitory assays identified tomatidine, a tomato-derived metabolite, as a potent HaT beta H inhibitor with strong binding affinity. In vivo bioassays confirmed tomatidine's inhibitory effects, reducing feeding and increasing mortality in H. armigera. Modulation in HaT(1H expression or activity disturbs the tyrosine metabolic pathway, with altered levels of tyramine, octopamine, and dopamine. These results highlight HaT(1H as a key regulator of OA biosynthesis, influencing insect feeding, locomotion, and overall survival. The present study also introduces tomatidine as a potential candidate for insect control, given its ability to disrupt HaT beta H function. This work provides new insights into the physiological roles of HaT beta H and offers promising avenues for developing targeted pest management strategies.
Keywords: Helicoverpa armigera; Octopamine biosynthesis; Tomatidine; Tyramine (1-hydroxylase (HaT(1H); Tyrosine metabolic pathway

From signals to sustenance: the role of biogenic amines in insect feeding behavior - Patil, Yogita P.; Joshi, Rakesh S. (Journal of Insect Behavior, 2025)
Insect feeding is a complex and finely-tuned behavior that notably impacts their physiological and metabolic processes. Chemical signals and cues, chemosensation, motor response, and physiological changes govern responses to food resources. The role of biogenic amines in regulating feeding is essential, as they significantly affect locomotory changes and nutrient assimilation. Octopamine, tyramine, dopamine, serotonin, and other biogenic amines are neuromodulators, neurotransmitters, and neurohormones. Octopamine and tyramine have contrasting effects on food-seeking and foraging behavior regulation. The interaction among biogenic amines and their respective receptors initiates diverse signaling pathways by modifying the concentrations of intracellular secondary messengers like Ca2+, AMP, and other molecules. These signal transductions regulate various physical and metabolic processes, directly influencing feeding behavior and digestive physiology. Furthermore, dopamine triggers a negative response, whereas serotonin plays a positive role in regulating feeding behavior. Biogenic amines underlie synchronized and interconnected molecular mechanisms, along with unique individual effects. It is fascinating to consider these interrelated activities and the impacts of bioamine on insect feeding behavior. In this review, we discuss the roles of insect biogenic amines and their cross-talk in insect feeding and foraging behavior.
Keywords: Biogenic amines; feeding behavior; octopamine; Signal transduction; tyramine

LDH-dsRNA nanocarrier-mediated spray-induced silencing of juvenile hormone degradation pathway genes for targeted control of Helicoverpa armigera - Joshi, Kaumudi S.; Barvkar, Vitthal T.; Hadapad, Ashok B.; Hire, Ramesh S.; Joshi, Rakesh S. (International Journal of Biological Macromolecules, 2025)
Helicoverpa armigera, a devastating agricultural pest, poses significant threats to global crop productivity. Targeting the Juvenile Hormone (JH) degradation pathway may offer a promising approach for pest management, given its pivotal role in insect development and reproduction. In this study, we developed a nanoclay-based formulation of double-stranded RNA (dsRNA) targeting three key JH degradation pathway genes: Juvenile Hormone Esterase (HaJHE), Juvenile Hormone Epoxy Hydrolase (HaJHEH), and Juvenile Hormone Diol Kinase (HaJHDK). Expression analysis revealed tissue and stage-specific patterns of these genes, with qRT-PCR confirming high expression levels of specific isoforms in key developmental transition: the pre-pupal stage. Treatment with bacterially expressed dsRNAs achieved >50 % silencing of target genes, resulting in delay in larval-to-pupal transitions. Bioassay demonstrated that treatment with LDH-based dsRNA nanocarrier resulted in downregulation of target genes, causing developmental delays, including prolonged larval and pupal stages. Metabolomic analysis further indicated reduced accumulation of JH degradation pathway metabolites, highlighting the pathway-specific action of dsRNAs. Furthermore, combinatorial application of dsRNAs resulted in higher mortalities compared to individual dsRNA application. These results suggest that the application of the LDH-based dsRNA nanocarrier formulation against H. armigera JH degradation pathway for spray-induced gene silencing could serve as a potential insect management strategy.
Keywords: Development; dsRNA; Helicoverpa armigera; Juvenile hormone; Layered double hydroxide; Nanocarrier

Novel bifunctional inhibitor of protease and α-amylase from Clitorea ternatea restricts the growth and development in Spodoptera frugiperda - Dongare, Pratiksha M.; Madage, Varsha A.; Deshpande, V. Neha; Joshi, Rakesh S.; Giri, Ashok P.; Pawar, Pankaj K. (International Journal of Biological Macromolecules, 2025)
An inhibitor molecule capable of inhibiting a wide range of digestive enzymes without affecting endogenous enzymes is always desirable. We report characterization of CteTAI (M.W. 14 kDa), a bifunctional inhibitor (BFI) protein from the seeds of Clitoria ternatea capable of inhibiting trypsin and alpha-amylase. It retains trypsin inhibition activity up to 60 degrees C and alpha-amylase inhibition up to 40 degrees C. Trypsin inhibition is stable across pH 1-12, while alpha-amylase inhibition is stable between pH 3-7. CteTAI is a noncompetitive inhibitor of trypsin and an uncompetitive inhibitor of alpha-amylase. It selectively inhibits proteases and alpha-amylases from various sources, without affecting alpha-amylase from human saliva and Bacillus spp. Proteomic analysis identified CteTAI as a bifunctional inhibitor exhibiting 41 % similarity to a bifunctional inhibitor from Sesbania bispinosa. Feeding Spodoptera frugiperda larvae with CteTAI-infused diet impaired energy metabolism, resulting in undernourished larvae and malformed adults incapable of flight and mating. Key nutritional indices (RGR, RCR, %ECI, %FDI) were severely reduced, indicating that CteTAI disrupts growth and development by inhibiting multiple protease and alpha-amylase isoforms. Biochemical characterization of newly identified CteTAI suggests its potential application in crop protection.
Keywords: alpha-Amylase inhibitors; Bifunctional inhibitor; Clitoria ternatea; Protease inhibitors; Spodoptera frugiperda

Mechanistic insights in the role of trehalose transporter in metabolic homeostasis in response to dietary trehalose - Chaudhari, Bhagyashri Y.; Nichit, Vikram J.; Barvkar, Vitthal T.; Joshi, Rakesh S. (G3-Genes Genomes Genetics, 2026)
Trehalose is the major sugar in insect hemolymph and plays a diverse role. Its level is regulated by the dynamics of biosynthesis and distribution by sugar transporters. The metabolic balance between trehalose synthesis and uptake remains poorly understood, despite its critical role in homeostasis. Here, we examined the role of the putative gut-specific sugar transporter, HaST46, in regulating trehalose levels in Helicoverpa armigera, a model Lepidopteran pest. Analysis of publicly available transcriptomics, proteomics data, and qRT-PCR study suggests that HaST46 showed localization in the posterior midgut and its expression alters in response to dietary contents. The liquid chromatography-mass spectrometry (LC-MS) analysis of HaST46 overexpressing Sf9 cells indicated that trehalose transport is preferred over glucose. HaST46 expression was found to be modulated tissue-specific manner in response to dietary trehalose availability. Furthermore, trehalose synthesis genes were found to be downregulated in the case of a 50 mM trehalose diet. This suggests that a potential increase in exogenous trehalose uptake may attenuate its endogenous synthesis. HaST46 overexpression and silencing lead to altered trehalose levels in the insect, while also having impact on trehalose metabolizing enzymes. Overall, our findings reveal the role of gut predominant sugar transporter, HaST46, in metabolic fine-tuning between exogenous trehalose uptake and endogenous synthesis.
Keywords: gut; Helicoverpa armigera; Metabolism; sugar uptake; transporters; trehalose